Intelligent Object Manipulation for a Wheelchair-Mounted Robotic Arm - R. A. M. Abayasiri; A. G. B. P. Jayasekara; R. A. R. C. Gopura; Kazuo Kiguchi (Journal of Robotics)
Over the years, intelligent wheelchairs have been developed to fulfill the needs of wheelchair users by gathering information from the environment to make autonomous decisions. This paper proposes an intelligent object manipulation algorithm that leverages users’ intentions, past experiences, and preferences. To gather the necessary information for object placement, a human study involving 20 healthy participants was conducted. The study included two situation-based object placement scenarios and object placement when objects were given in pairs. Building on the authors’ previously developed electromyography-based wheelchair navigation algorithm, a semiautonomous object manipulation algorithm was developed. This new algorithm was tested in the CoppeliaSim simulation environment by replicating the tasks performed in the human study. The object arrangements in the simulation were then compared to the results from the human study. The findings indicate that the implemented object manipulation algorithm successfully replicated the outcomes observed in the human study. The application of this controller is expected to significantly enhance accessibility for individuals with impaired motor functionalities in addition to their ambulatory impairments. This development represents a significant step forward in creating user-friendly and adaptive assistive technologies for wheelchair users.